Long-term evolution of supercritical black hole accretion with outflows: a subgrid feedback model for cosmological simulations - Hu, Haojie; Inayoshi, Kohei; Haiman, Zoltán; Quataert, Eliot; Kuiper, Rolf (The astrophysical journal, 2022)
We study the long-term evolution of the global structure of axisymmetric accretion flows onto a black hole (BH) at rates substantially higher than the Eddington value (), performing 2D hydrodynamical simulations with and without radiative diffusion. In the high-accretion optically thick limit, where the radiation energy is efficiently trapped within the inflow, the accretion flow becomes adiabatic and comprises turbulent gas in the equatorial region and strong bipolar outflows. As a result, the mass inflow rate decreases toward the center as with p ∼ 0.5-0.7 and a small fraction of the inflowing gas feeds the nuclear BH. Thus, super-Eddington accretion is sustained only when a larger amount of gas is supplied from larger radii at ≳100-1000 . The global structure of the flow settles down to a quasi-steady state in millions of the orbital timescale at the BH event horizon, which is ≳10-100 times longer than that addressed in previous (magneto-)RHD simulation studies. Energy transport via radiative diffusion accelerates the outflow near the poles in the inner region but does not change the overall properties of the accretion flow compared to the cases without diffusion. Based on our simulation results, we provide a mechanical feedback model for super-Eddington accreting BHs. This can be applied as a subgrid model in large-scale cosmological simulations that do not sufficiently resolve galactic nuclei, and to the formation of the heaviest gravitational-wave sources via accretion in dense environments.
Gesehen am 19.08.2022